2017
DOI: 10.3126/jkmc.v6i1.18581
|View full text |Cite
|
Sign up to set email alerts
|

A study on parental age, pregnancy events and autism spectrum disorders

Abstract: Background: Autism spectrum disorder (ASD) is a neurological disorder which usually appears before the age of 3. Several genetic or environmental factors may be involved in onset of Autism Spectrum Disorder. Objectives: To fi nd relationship of Autism Spectrum Disorder with different maternal factors and events during pregnancy. Methodology: This is a retrospective case control study with total of 104 children of age 3-15 years as a sample, 52 were cases and 52 were controls. The study unit was selected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Ultimately, five studies that met the inclusion criteria were included in this meta-analysis, including one cohort study 11) and four case-control studies 3,10,19,20) with a total sample size of 3088 children. Figure 1 presents a patient selection flow chart.…”
Section: Study Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, five studies that met the inclusion criteria were included in this meta-analysis, including one cohort study 11) and four case-control studies 3,10,19,20) with a total sample size of 3088 children. Figure 1 presents a patient selection flow chart.…”
Section: Study Descriptionmentioning
confidence: 99%
“…9) Studies have investigated the association between fetal nuchal cord and ASD in children. 3,10,11) On reported that fetal nuchal cord was associated with ASD, 3) while others did not. 10,11) Moreover, there are limited reviews on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation